Memorializing Martin: The Living Dream of Martin Luther King Jr. in Junction City, Kansas - Claxton, Haley (Kansas State University, The Chapman Center for Rural Studies, 2014)
The legacy of Martin Luther King Jr. is immortalized in Junction City, Kansas, by the grassroots efforts of both individuals and the community, in an annual celebration, marches, and a memorial park. This study was made possible using sources from the Geary County Historical Society and Dorothy Bramlage Public Library.
Haley Claxton, “Memorializing Martin: The Living Dream of Martin Luther King Jr. in Junction City, Kansas,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/234.
Keywords: African American history; Junction City; Martin Luther King Jr.; Exodusters; NAACP; Kansas State University